Heat Transfer Characteristics in Vertical Tubular Baffle Internal Reboiler through Dimensional Analysis - Susmiati, Yuana; Purwantana, Bambang; Bintoro, Nursigit; Rahayoe, Sri (Faculty of Engineering Universitas Indonesia, 2022)
Heat transfer in shell and tube heat exchangers is in general described in terms of the relationships of Nuselt, Prandtl, and Reynold dimensionless numbers. One of the parameters of heat exchanger performance is convective heat transfer coefficient (h), and mathematical model can predict it. This study aimed to find out the relationship of the parameters that affected the performance of vertical tubular baffle internal reboiler during ethanol distillation. The mathematical model was developed by a dimensional analysis with the π-Buckingham method. Several influencing parameters during the distillation process were identified to develop a mathematical model. The study was carried out on the distillation process of low-concentration ethanol, i.e., 10%, 20%, 30% using internal reboilers with different tube sizes, i.e., diameters of 1.27 cm, 2.54 cm, 3.81 cm and height of 4 cm, 6 cm, 8 cm, to obtain the value of h observation. Based on the results of the study, a heat transfer model was obtained, i.e., (Formula Presented), where Nu, Re, D, L, T, Cp, v, ρ, and k, are respectively Nuselt, Reynold, tube diameter, tube height, temperature, heat capacity, velocity, mass density, and thermal conductivity of the fluid (material). This model can be used to determine h prediction, and the result is following h observation with equation y = 0.98x and R² = 0.99. Based on the results of the study, it is known that differences in material concentration, diameter, and height of the reboiler tube affect the value of h